A refined chronology for the Gravettian sequence of Abri Pataud. Issue 141 (April 2020) - Douka, Katerina; Chiotti, Laurent; Nespoulet, Roland; Higham, Thomas
Abstract: Abri Pataud (France) is the type site in studies focusing on the appearance of modern humans and the development of classic Upper Paleolithic technocomplexes in Europe. It contains important evidence of successful adaptation strategies of modern humans to new territories and in response to sharply changing climatic conditions that characterized Marine Isotope Stages 3 and 2. Despite being for decades one of the best excavated and most studied Paleolithic sites, the chronology of Abri Pataud has lacked precision and revealed large discrepancies. The chronology of the lowermost part of the sequence (Levels 14–5) was refined in 2011 with the publication of 32 new radiocarbon determinations, mainly from the Aurignacian levels. In contrast, the Gravettian levels (Levels 5–2) remained poorly dated until now. Here, we present 18 new radiocarbon dates on cut-marked animal bones from the Gravettian part of the site, which complete the dating of this important sequence. The determinations are analyzed using Bayesian statistical modeling, and the results allow us to place the start of the Gravettian at the site between ∼33, 000 and 32, 000 cal BP (∼29, 000–28, 000 BP). We discuss the succession of the Gravettian facies across the sequence (Bayacian, Noaillian, Rayssian), as well as the likely duration of each archaeological level. With a total of more than 50 radiocarbon determinations, Abri Pataud offers secure information for the appearance and development of the technocomplexes linked with early modern humans and their establishment in western Europe. Based on published genetic data, it appears that it is the Gravettian hunter-gatherers and subsequent human groups, rather than the earlier Aurignacian and pre-Aurignacian groups, that contributed to the genetic signature of later and living Europeans. Hence, elucidating the precise timing of the Gravettian appearance has broad implications in our understanding of late human evolution across Europe.